Identification and Expression Analysis of Genes Induced in Response to Tomato chlorosis virus Infection in Tomato - Şahin-Çevik, Mehtap (Plant Pathol J, 2019)
Tomato (Solanum lycopersicum) is one of the most widely grown and economically important vegetable crops in the world. Tomato chlorosis virus (ToCV) is one of the recently emerged viruses of tomato distributed worldwide. ToCV-tomato interaction was investigated at the molecular level for determining changes in the expression of tomato genes in response to ToCV infection in this study. A cDNA library enriched with genes induced in response to ToCV infection were constructed and 240 cDNAs were sequenced from this library. The macroarray analysis of 108 cDNAs revealed that the expression of 92 non-redundant tomato genes was induced by 1.5-fold or greater in response to ToCV infection. The majority of ToCV-induced genes identified in this study were associated with a variety of cellular functions including transcription, defense and defense signaling, metabolism, energy, transport facilitation, protein synthesis and fate and cellular biogenesis. Twenty ToCV-induced genes from different functional groups were selected and induction of 19 of these genes in response to ToCV infection was validated by RT-qPCR assay. Finally, the expression of 6 selected genes was analyzed in different stages of ToCV infection from 0 to 45 dpi. While the expression of three of these genes was only induced by ToCV infection, others were induced both by ToCV infection and wounding. The result showed that ToCV induced the basic defense response and activated the defense signaling in tomato plants at different stages of the infection. Functions of these defense related genes and their potential roles in disease development and resistance to ToCV are also discussed.